1994
DOI: 10.1002/hpm.4740090203
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal health improvement on perinatal survival: Cost‐effective alternatives

Abstract: Each year, an estimated half million women die from complications related to child birth either during pregnancy, delivery or within 42 days afterwards. When pregnant women have complications, their infants are at greater risk of becoming ill, permanently disabled or dying. For every maternal death, there are at least 20 infant deaths: stillbirths, neonatal or postneonatal deaths. Altogether, an estimated 7 million infants each year die perinatally (stillborn or deaths within the first week of life). Low cost,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…For some interventions or packages of care, promising results in efficacy trials have included, or subsequently led to, evaluations of their cost-effectiveness. 671,672 In general, however, attempts at costing interventions have included posthoc data collection or extrapolation, which are not optimal for this kind of analysis. 673 Studies in developed countries have shown that early initiation of antenatal care is among the most cost-effective strategies for reducing neonatal mortality.…”
Section: Cost-effectiveness Of Community-based Interventionsmentioning
confidence: 99%
“…For some interventions or packages of care, promising results in efficacy trials have included, or subsequently led to, evaluations of their cost-effectiveness. 671,672 In general, however, attempts at costing interventions have included posthoc data collection or extrapolation, which are not optimal for this kind of analysis. 673 Studies in developed countries have shown that early initiation of antenatal care is among the most cost-effective strategies for reducing neonatal mortality.…”
Section: Cost-effectiveness Of Community-based Interventionsmentioning
confidence: 99%
“…13 Overall, pregnancy and delivery complications are implicated in more than half of newborn deaths.…”
Section: Maternal Health and Antenatal Carementioning
confidence: 99%
“…The main causes of maternal mortality are postpartum hemorrhage, inappropriate timing and spacing of children, too many pregnancies, unsafe abortion, and insufficient prenatal care and care during delivery (WHO 1990). In countries with high fertility rates, major reductions in maternal and infant deaths result both from reductions in the number of pregnancies through family planning and from improved obstetric care (Walsh et al 1994).…”
mentioning
confidence: 99%